Employees Work Engagement: Correlations with Employee Personal Characteristics, Organizational Commitment and Workplace Happiness - Tugade, Guinevere Yvonne G.; Arcinas, Myla M. (Future Science / FSH-PH Publications, 2023)
Using data collected from 76 employees of a manufacturing company in Manila, Philippines, this study conducted a correlation analysis to determine the relationship between the level of their engagement at work and their personal characteristics, organizational commitment in the workplace, and job satisfaction. A self-administered structured survey questionnaire was use in the survey. The collected data was analyzed using descriptive statistics to determine the mean scores, frequencies, and percentages, and parametric inferential statistics were employed to examine the correlations between variables. The results indicate a high level of employee work engagement and job satisfaction, as well as a moderate level of employee organizational commitment. Employee age, position and monthly salary were significantly correlated with employee work engagement. The level of employee engagement increases with age, position and income. Results also revealed a significant and strong positive correlation between the level of employee engagement and employee happiness at work. Implications for practices are offered.